DEVELOPMENT OF NATURAL REST ZONES, RECREATION ZONES - Salimov Arifdjan Muslimovich; Kurganov Uktamjon, Kurganova Zulayho (Academia Science Repository, 2023)
This article discusses the formation and origin of natural recreation zones, provides practical suggestions for the restoration of recreation zones and their improvement.